Cafe Bah!: Nasi 7 benua with ice lemonade / Muhd Azhar M Ikhsan ... [et al.] - M Ikhsan, Muhd Azhar; Abu Bakar, Surayya; Nazri, Syahminisa; Shaharin, Syasya Umira; Mohd Asy'ari, Umi Alyah Farhani (2021)
Our main objective in running this business is to provide an opportunity for all communities to taste the variety of rice that exist in Malaysia. Moreover, one of our mission is to sell this special dish with a cheap and affordable price that is comparable to its quality, taste and deliciousness. While the crucial vision in our business is to be known as the best place in serving the best lunch food. Furthermore, our business also has sufficient and well-organized administrative members for every sector such as manager, administration, marketing, operation and financial. The team cooperate and work very hard to manage the business and to gain more profit for every sale. Cafe Bah! Sdn Bhd is a partnership business that located at Sabah and we believe that Sabah is the best location for us to achieve our target. Most of the residents there are from medium range income and we provide the best price for them. Hence, we can clearly see our opportunity that our business has the potential to success in the future if we managed it efficiently